Investigação da influência de 2,5-dimercapto-1,3,4-tiadiazol nas propriedades eletroquímicas de polipirrol e nanotubos de carbono - Capucci, Hildo Henrique Grediaga (2012)
Currently, portable electronics are becoming smaller, requiring energy storage devices, compatible with their size, such as supercapacitors. In this context, composites materials composed of conducting polymers and carbon nanotube (CTN) have been extensively researched for using as electrodes in supercapacitors. The conducting polymers increase the electronic conductivity and CTN reinforces mechanically and stabilizes thermally the conducting composite. This study has as main objectives the synthesis and characterization of composite Polypyrrole (PPy) / poly 2,5 dimercapto-1,3,4-thiadiazole (PDMcT)/ CTN and its application as electrodes in supercapacitors Type I. There is a need to control the anodic charge of the PDMcT film present in the ternary composite to ensure a good electrochemical response. This control was performed by successive cycling of the PDMcT film using cyclic voltammetry until the anodic charge was remained constant. Based on the results of infrared analysis (IR), X-ray diffraction, thermogravimetric analysis (TGA) and scanning electron microscopy (SEM) was possible to prove that the ternary composite was synthesized chemically and electrochemically. The composites synthesized electrochemically were characterized by cyclic voltammetry and charge and discharge tests. The ternary composite of Ppy/PDMcT/CTN and binary of Ppy/CTN synthesized electrochemically showed the highest values of anodic charge, specific capacitance, specific power and coulombic efficiency when compared with the values obtained for the composites PDMcT/CTN and Ppy/PDMcT and their constituent materials. The capacitor device of Type I composed of ternary composites synthesized electrochemically with anodic charges of PDMcT/CTN and Ppy 1,3 mC and 1000 mC, respectively, were galvanostatically tested. The capacitance charge and discharge values obtained were 353,1 F g-1 and 348,8 F g-1, respectively, showing coulombic efficiency of 98.8% and power of 10,240 KW after 1000 cycles. However, the same device with anodic charges PDMcT / Ppy CTN and 4.9 mC and 250 mC, respectively, resulted the values of capacitance charge and discharge of 193 F g-1 and 180 F g-1, respectively, with a coulombic efficiency of 93.48% and a power of 22,860 KW kg-1 after 1000 cycles. These results indicate a good reversibility redox of the ternary composite and a synergistic effect between the constituent materials. The Ppy and the PDMcT remained active during the charge and discharge processes and therefore both helped to intensify the electrochemical properties of the ternary composite. Then, the ternary composite Ppy / PDMcT / CTN is a promising material as electrodes for supercapacitors Type I.